Improving high temperature fretting fatigue performance of nickel-based single crystal superalloy by shot peening. (June 2023) - Yuan, Tianyu; Dou, Min; Liu, Lu; Li, Lei; Sun, Shouyi; Hu, Chuanyun
Highlights: Shot peening improves the fretting fatigue lives of a nickel-based single crystal superalloy at 600 °C by more than 200 %. The surface integrity of the nickel-based single crystal after shot peening treatment has been investigated. Strengthening mechanism of shot peening for fretting fatigue of nickel-based single crystal alloys is revealed. Abstract: Fretting fatigue (FF) is one of the main causes of turbine blade failure. In this study, the FF tests of a nickel-based single crystal (NBSC) superalloy treated by shot peening (SP) are conducted at 600 °C. Results show that the FF lives of shot-peened specimens are improved by up to 4 times compared to the unpeened ones. SP increases the dislocation density of the surface layer, which results in the increased hardness, and the maximum compressive residual stresses (CRS) can reach to −1016 MPa. The large CRS reduces the true stress acting on the fretting contact region, and high-density dislocation retards the crack initiation and propagation, both of which contribute to the prolonged FF life. This work provides an effective strategy for the anti-fretting fatigue strenghening of NBSC superalloy.